Water and Wastewater Services in the Danube Region : Bosnia and Herzegovina Country Note - World Bank (Washington, DC, 2015)
In order to evaluate the sustainability of services in the region, an overall sector maturity assessment was done taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess sector maturity is included in the annex of the state of the sector Regional Report from the Danube Water Program. The outcomes of this assessment for the Bosnia and Herzegovina water sector are displayed in Figure 10, which also shows average and best practices in the Danube region. The BiH sector maturity score is 57, which is close to the Danube average maturity of 64. The assessment shows that, on average, the country performs well in terms of access to piped water and flush toilets, and customer satisfaction. With regard to the BiH water sector, the main deficiencies identified through the sector maturity assessment are level of investment, staffing level, and wastewater treatment coverage.